Ultra-fast densification of boron carbide by flash spark plasma sintering. (15th April 2016) - Niu, Bo; Zhang, Fan; Zhang, Jinyong; Ji, Wei; Wang, Weimin; Fu, Zhengyi
Abstract: A novel method, Flash Spark Plasma Sintering (FSPS), combining flash sintering and electric field assisted sintering was used to densify B4 C ceramics. B4 C powder was densified up to 99.2% in 1 min with limited grain size increase at 1931 °C under an applied pressure of 15.3 MPa. TEM analysis of the grain structure of the resulting ceramics suggests that the Joule heating and sparking initiated by the pulsed current are highly localized to particle interfaces and contribute significantly to the character of densification. We show that plastic deformation under high current and low pressure is the dominant densification mechanism. Graphical abstract: